Informed learning design: teaching and learning through engagement with information. Issue 3 (16th April 2019) - Maybee, Clarence; Bruce, Christine Susan; Lupton, Mandy; Pang, Ming Fai
ABSTRACT: While higher education teachers are able to use information in sophisticated ways to learn and communicate within their disciplines, they may not be accustomed to teaching their students to use information creatively and reflectively to support their work in a course. This article introduces informed learning design, a curriculum design model by which teachers specifically enable students to learn course content through intentional engagement with information. Drawing from informed learning pedagogy and the variation theory of learning, the design model outlines an instructional pattern for enabling student awareness of critical aspects and features of the object being studied related to both information use and course content.